Structural stability and a characterization of Anosov families. Issue 3 (3rd July 2019) - Muentes Acevedo, Jeovanny de Jesus
ABSTRACT: Anosov families are non-stationary dynamical systems with hyperbolic behaviour. Non-trivial examples of Anosov families will be given in this paper. We show the existence of invariant manifolds, the structrural stability and a characterization for a certain class of Anosov families.